BMBF‐Projekt „Multi‐Phase"︁1. Issue 7 (29th May 2013) - Becker, Marc; Tuinier, Martin; Rollbusch, Philipp; Ludwig, Martina; Franke, Robert; Grünewald, Marcus; Schlüter, Michael; Grünewald, Marcus; Lausch, Hans‐Rolf; Schlüter, Michael
<x xml:space="preserve">Abstract</x> The BMBF project "Multi‐Phase" seeks to optimize multiphase reactors utilizing scale‐independent models, measurement techniques and apparatuses. The project members link their competences in academic fundamental research, small and medium‐sized companies with expertise on measurement technologies and design and operation of industrial processes. Evonik Industries AG transfers the laboratory data and models to industrial scale and provides the results to the project partners. Significant energy efficiency as well as reduced CO2 emissions are expected.